Transient Aurein 1.2 pores in prokaryotic model bilayers explored by coarse-grain molecular dynamics simulations: as glycolipid content increases, pore lifetime decreases - Balatti, Galo Ezequiel (2023)
The Aurein 1.2 is an anuran antimicrobial peptide (AMP) with a proven lytical activity against bacterial membranes. Previously, we found a differential action of aurein by both experimental and computational methods. This differential action was over membranes of two related probiotic strains, where the main differences between membranes were the number of glycolipids on lipid composition. In the present work, we focused on the differential behavior of the aurein 1.2 at its interaction with bacterium model membranes with different amounts of glycolipids in their composition. We carried out extensive molecular dynamics (MD) simulations by using the coarse-grain force field MARTINI and raising up differential mixtures of phosphatidylglycerol (PG), phosphatidylethanolamine (PE) and monogalactosylglycerol (MG). We found a correlation between the presence of MG in PG/PE mixtures and the difficulty of aurein to stabilize pore structures, suggesting an AMP resistance factor encoded in the lipid composition of the membrane. Through this study, we hope to shed light on a possible resistance mechanism to AMPs related with the glycolipid content of diverse types of bacterial membranes.